FAKTOR – FAKTOR YANG MEMPENGARUHI PENGETAHUAN ORANG TUA TERHADAP GIZI SEIMBANG ANAK DI KB/TK PELANGI IMPIAN BOJONNGSARI DEPOK 2017 - Fitri Ramadhani (STIKes IMC Bintaro, 2017)
Good nutritional status is the main requirement of quality human resources, especially for toddlers. Toddlers who experience disturbance or malnutrition at an early age will disrupt growth, causing pain and death. Nutritional disorders are generally caused by lack of intake, infection and most importantly the lack of parental attention. Parent Knowledge of Balanced Nutrition of Children in KB / TK Pelangi Dream Bojongsari Depok. This research uses quantitative research type with cross sectional study design, that is studying the relationship between dependent variable of child nutrition status and independent variable. The population in this research is parents in TK Pelangi Dream in 2017. Univariate data analysis using frequency while bivariate analysis using chi sqare. Most of them are aged 5-6 th as many as 43 respondents or approximately (71.7%). Male gender was 38 respondents or approximately (63,3%). Normal weight as many as 48 respondents or approximately (80.0%). Frequency of eating 3x / day as many as 60 respondents or approximately (100.0%). High school maternal education as many as 35 respondents (58.3%). Working mother who did not work as much as 37 respondents or about (61,7%). Monthly income ≥ Rp. 4,000,000, - as many as 60 respondents or approximately (100.0%). Parents are advised to pay attention to the child's diet.